Empowerment Bidai Craft As A Solution On Eradicating Unumployment In The Borderland Area - Rissa Ayustia; Usman Usman (Journal of International Conference Proceedings (JICP), 2019)
The problem of border areas in Indonesia has not found a bright spot to date. The main problem faced by border communities is Unemployment. Unemployment must be addressed appropriately because it has an impact on people's economic lives. Therefore, there must be a solution to reduce the amount of unemployment in the border area. The purpose of this study was to determine the extent of empowerment of bidai craft as a solution to reduce unemployment in the border area and the participation of the village government. Data collection techniques in this study used interview and observation techniques. Data analysis by data collection, reduction, presentation and data verification. The research method uses qualitative in order to get a comprehensive picture. The results of this study indicate that 1) the root of the problem of unemployment 2) Empowerment of the splint can be used as a solution to overcome unemployment in the border area 3) The participation of the village government.